LEARNING PROCESS OF FRACTION OPERATIONS IN STUDENTS WITH INTELLECTUAL DISABILITIES - Dela Devita; Nurhidayati Nurhidayati; Desrina Hardianti; Dwi Desmayanasari (Hipotenusa Journal of Research Mathematics Education (HJRME), 2025)
This study examines the learning process of fractional number operations in students with intellectual disabilities. Using a qualitative descriptive method. the study focuses on students and teachers in grade IX. Data collection is conducted through observation, interviews, and documentation techniques. The research instruments include observation guidelines and interview protocols. The results of the study indicate that: (1) students experience difficulties in understanding the concept of fractions, particularly in adding fractions using the concept of regrouping and in subtracting fractions by borrowing; (2) the learning process of fractional number operations for students with intellectual disabilities reveals that teachers have not prepared Individual Learning Programs (ILPs) to guide individual learning during the teaching preparation stage; (3) during the implementation of lessons, teachers have not fully utilized available learning media, and the methods employed tend to be monotonous; and (4) although evaluations are aligned with the lesson plan, the time allocated for conducting evaluations needs to be maximized. A suitable variety of learning methods and media can assist students with intellectual disabilities in understanding the material.